2016
DOI: 10.1080/1828051x.2016.1221748
|View full text |Cite|
|
Sign up to set email alerts
|

Pedigree analysis of Cashmere goat breed of South Khorasan

Abstract: The genealogical data of Cashmere goat breed of South Khorasan province of Iran was analysed in this study. Records from a total of 10,635 animals collected during 1988-2014 from 20 registered flocks were analysed for evaluating pedigree parameters. The reference population was defined as the living reproductive animals born from 2010 till 2014. The average inbreeding coefficient in the studied breed was about 0.07% (ranging from 0 to 25%). In addition, the average inbreeding coefficient for the reference popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
2
0
1
Order By: Relevance
“…Tomar et al ( 41 ) reported that the generation interval was 2.04 years for Beetal goats. Similar results were observed in other breeds of goats ( 34 , 35 , 42 ). The generation length is ~4 years for most goats.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Tomar et al ( 41 ) reported that the generation interval was 2.04 years for Beetal goats. Similar results were observed in other breeds of goats ( 34 , 35 , 42 ). The generation length is ~4 years for most goats.…”
Section: Discussionsupporting
confidence: 90%
“…A small fraction of high inbreeding individuals may be caused by natural mating or poor management. The average inbreeding value in the entire studied population was 4.50%, which is lower than that in the cashmere goat breed of the South Khorasan and Iranian Adani goat breeds reported by Joezy-Shekalgorabi et al ( 34 , 35 ). However, Illa et al ( 14 ) reported that the average inbreeding coefficient in Nellore sheep was 3.32%, which was lower than that in the IMCG population.…”
Section: Discussioncontrasting
confidence: 58%
“…This could be attributed to the fact that Galla goats tend to have a rapid growth rate as compared to SEA goats which makes them be bred at a younger age. Similar values were reported by 29 , 30 for South Khorasan Cashmere and Creole Goats in America, however, a higher generation interval of 5.28 years was reported by 31 in Brazilian Marota goats. Lower figures for the generation interval of 3.3, 2.77, and 3.3 years were reported by 3 , 10 , 28 in Jamunapari, Spanish Murciano-Granadina and Markhoz goats.…”
Section: Discussionsupporting
confidence: 85%